PROBLEMS OF EDUCATION OF LITERATED YOUTH IN THE WORKS OF OUR GREAT THINKERS (TAMADDUN NURI JURNALI, 2025)
In this article, the author studies the scientific heritage of Central Asian thinkers and analyzes the use of their scientific views in the education of youth. The knowledge we receive today determines our future. Our main task is to solve urgent problems of modern pedagogy, education and upbringing of youth.